BUDAYA KERJA DAN IKLIM ORGANISASI PENGARUHNYA TERHADAP KINERJA TENAGA MEDIS DI UNIT RAWAT INAP RSUD RAJA MUSA SUNGAI GUNTUNG - jurnalmap map (MAP (Jurnal Manajemen dan Administrasi Publik), 2022)
The purpose of this study is to describe the work culture and climate of the organization's influence on the performance of medical personnel in the Inpatient Unit of Raja Musa Sungai Guntung Hospital. This research approach is a quantitative study using a questionnaire as a tool to collect data. The total sample of 42 respondents, namely all medical personnel in the RSUD Raja Musa Sungai Guntung were used as respondents in the study. The results showed that work culture partially influenced the performance of medical personnel. Organizational climate has a partial effect on the performance of medical personnel. F test results of work culture and organizational climate simultaneously have a positive and significant effect on the performance of medical personnel. The results of the coefficient of determination test indicate that the influence of work culture and organizational climate on the performance of medical personnel by 75.5%, while the remaining 24.5% can be explained by other variables outside of the research variables.